Sorption of heavy metals from complex solutions using ion exchangers obtained from peanut shells - Karimova , Dilfuza; Izatillayeva , Charos; Abdurashidova , Guljahon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the heavy metal sorption properties of ion exchangers obtained from peanut (Arachis hypogaea) shells using various chemical modification methods in complex (multi-component) solutions. The research focuses on studying the influence of different modification techniques (H₃PO₄, KOH, , mercaptoacetic acid, iron oxides) on sorption capacity, inter-ionic competition mechanisms, and selectivity characteristics. The results indicate that the modified ion exchangers exhibit high selectivity in complex solutions, with Pb²⁺ ions predominating over other metals in most cases